A comparative study on microstructural and mechanical behaviour of spot welded Ti-6Al-4V alloy in as-welded and solution treated condition. Issue 3 (3rd July 2022) - Kumar, Bikash; Dwibedi, Swagat; Bag, Swarup; Mahapatra, Manmohan; Gupta, Roshan
ABSTRACT: The current experimentation emphasises on the diversification in metallurgical transformation under solution treatment, which governs the solidification rate and can trigger the final mechanical behaviour of the welded structure. In the present work, a thin sheet (750 μm) of Ti-6Al-4V alloy is joined using resistance spot welding process in overlap configuration at varied weld time cycles of 30, 50, and 70. Further, in order to explore metallurgical aspects and associated influence on mechanical behaviour, post-weld heat treatment (PWHT) is performed. The weld pad is heated up to β -transus temperature ( 915°C) for 60 min, consequently cooled by water quenching method. It is opined that the welding heterogeneity that arises at welding can be homogenised by gradual heating and cooling cycles in the PWHT cycle. Upon increasing weld time from 50 → 70 cycles, mechanical properties are improved. Therefore, 70 cycles is regarded as the optimised weld time. Coarsening of α -lath within the prior β -grain boundary is confirmed in the weld zone of as-welded specimens. On the other hand, application of solution treatment found is to be advantageous since it changes the mode of failure from interfacial to pullout, which is always desirable. Improved tensile-shear load bearing capacity (TSLBC) and extension are indicated by pullout failure accompanied by solution treatment.